Identification of metabolic vulnerabilities of receptor tyrosine kinases-driven cancer - Nan Jin (Nature Portfolio, 2019)
Cancer subtypes may have distinct metabolic vulnerabilities that can be exploited for therapeutic interventions. Here, the authors show that in lung cancer, genetic activation of distinct oncogenic receptor tyrosine kinases results in unique metabolic liabilities and, in particular, EGFR aberrant cancers rely on the serine biosynthetic pathway while FGFR aberrant cancers rely on glycolysis.